Technical performance analysis of a newly promoted professional futsal team: Evidence from Rafhely FC in the 2024–2025 Indonesian pro futsal league - Muhammad Alief; Masrun; Ardo Okilanda; Vega Soniawan; Bram Sujadesman (CV. FOUNDAE, 2026)
Background: Newly promoted professional futsal teams often encounter challenges in adapting to the competitive demands of elite leagues, making objective performance evaluation essential for evidence-based coaching. Despite the growing interest in futsal performance analysis, studies examining season-long technical performance indicators in Indonesian professional clubs remain limited. Aim: This study aimed to evaluate the technical performance of Rafhely FC throughout the 2024–2025 Indonesian Pro Futsal League season using objective match performance indicators. Method: A quantitative descriptive design was employed using observational data from all 22 league matches. Match statistics, including goals scored, goals conceded, scoring time, dominant foot, shots on target, and match outcomes, were collected through video-based performance analysis and analysed using descriptive statistics. Results: Rafhely FC demonstrated inconsistent performance throughout the season, recording four wins (18.18%), two draws (9.09%), and sixteen losses (72.73%). The team showed greater goal-scoring productivity during the final ten minutes of matches, predominantly using the right foot. However, limited shot conversion efficiency and a higher number of goals conceded than scored reduced overall competitive performance. Conclusion: The findings indicate that Rafhely FC requires improvements in attacking efficiency, defensive organisation, and tactical consistency. Objective technical performance analysis provides valuable evidence for supporting coaching decisions and strategic planning in professional futsal.